“KITAB-I DIYARBAKRIYYA” IS A MAJOR SOURCE ON THE TIMURID PERIOD - Avazov Farrukh Azamat ogli (International Journal of Innovations in Engineering Research and Technology, 2023)
This article gives information about known historian Abu Bakr Tihrani-e and his historical essay “Kitab-i Diyarbakriyya”, also translations and editions of this source. This historical work is one of the main sources of the reign of the Sultan and Abu Said Mirza in the Timurid state and his relations with Ak Koyunlu and Kara Koyunlu Turkmens.